2020
DOI: 10.21203/rs.3.rs-59050/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When the Labs Closed: Graduate Students’ and Postdoctoral Fellows’ Experiences of Disrupted Research During the COVID-19 Pandemic

Abstract: Physical distancing measures in response to the COVID-19 pandemic resulted in widespread laboratory closures. This study aimed to examine the impact of this disruption on graduate students and postdoctoral fellows completing laboratory-based research in Canada. We used an anonymous online survey and semi-structured interviews to document the experiences of graduate students and postdoctoral fellows during laboratory closures and following the transition to working from home. We employed mixed-method analysis o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Yet, when the space at home is limited and several members of the household need a space to work, sharing the same workspace might become inevitable. In fact, in a survey conducted by Suart et al [30], it was found that only 48.6% of the respondents had a dedicated workspace, 31% were sharing their workspace with others and the remaining 20.4% were working in a variety of places in their homes. However, research shows that productivity decreases with lack of ability to adjust/personalize workspace as well as lack of storage space [31].…”
Section: Workpace Contextmentioning
confidence: 99%
“…Yet, when the space at home is limited and several members of the household need a space to work, sharing the same workspace might become inevitable. In fact, in a survey conducted by Suart et al [30], it was found that only 48.6% of the respondents had a dedicated workspace, 31% were sharing their workspace with others and the remaining 20.4% were working in a variety of places in their homes. However, research shows that productivity decreases with lack of ability to adjust/personalize workspace as well as lack of storage space [31].…”
Section: Workpace Contextmentioning
confidence: 99%
“…Graduate students have been found six times as likely to experience depression and anxiety as compared to the general population [13]. This problem has only been further exacerbated by the isolation and strain graduate students now feel as a result of the limitations imposed on their research work as a result of COVID-19 [14].…”
Section: The Problem Of Anxiety and Depression In Graduate Studentsmentioning
confidence: 99%
“…Student advocacy groups argue that the compounding effects caused by the pandemic, not only on research but also personal and social lives, simultaneously and globally, qualify all students for an extension, regardless of their stage of candidature. For example, a survey of doctoral and postdoctoral researchers in Canada shows that researchers experienced emotional challenges regardless of whether or not they could continue working during the pandemic (Suart et al 2020). The researchers who could access the lab experienced guilt for being able to work while their peers could not, and anxiety due to future uncertainties and the possibility of contracting the virus.…”
Section: Victoriamentioning
confidence: 99%